If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x(6x + -4) = 10 Reorder the terms: 8x(-4 + 6x) = 10 (-4 * 8x + 6x * 8x) = 10 (-32x + 48x2) = 10 Solving -32x + 48x2 = 10 Solving for variable 'x'. Reorder the terms: -10 + -32x + 48x2 = 10 + -10 Combine like terms: 10 + -10 = 0 -10 + -32x + 48x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-5 + -16x + 24x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-5 + -16x + 24x2)' equal to zero and attempt to solve: Simplifying -5 + -16x + 24x2 = 0 Solving -5 + -16x + 24x2 = 0 Begin completing the square. Divide all terms by 24 the coefficient of the squared term: Divide each side by '24'. -0.2083333333 + -0.6666666667x + x2 = 0 Move the constant term to the right: Add '0.2083333333' to each side of the equation. -0.2083333333 + -0.6666666667x + 0.2083333333 + x2 = 0 + 0.2083333333 Reorder the terms: -0.2083333333 + 0.2083333333 + -0.6666666667x + x2 = 0 + 0.2083333333 Combine like terms: -0.2083333333 + 0.2083333333 = 0.0000000000 0.0000000000 + -0.6666666667x + x2 = 0 + 0.2083333333 -0.6666666667x + x2 = 0 + 0.2083333333 Combine like terms: 0 + 0.2083333333 = 0.2083333333 -0.6666666667x + x2 = 0.2083333333 The x term is -0.6666666667x. Take half its coefficient (-0.3333333334). Square it (0.1111111112) and add it to both sides. Add '0.1111111112' to each side of the equation. -0.6666666667x + 0.1111111112 + x2 = 0.2083333333 + 0.1111111112 Reorder the terms: 0.1111111112 + -0.6666666667x + x2 = 0.2083333333 + 0.1111111112 Combine like terms: 0.2083333333 + 0.1111111112 = 0.3194444445 0.1111111112 + -0.6666666667x + x2 = 0.3194444445 Factor a perfect square on the left side: (x + -0.3333333334)(x + -0.3333333334) = 0.3194444445 Calculate the square root of the right side: 0.565194165 Break this problem into two subproblems by setting (x + -0.3333333334) equal to 0.565194165 and -0.565194165.Subproblem 1
x + -0.3333333334 = 0.565194165 Simplifying x + -0.3333333334 = 0.565194165 Reorder the terms: -0.3333333334 + x = 0.565194165 Solving -0.3333333334 + x = 0.565194165 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + x = 0.565194165 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + x = 0.565194165 + 0.3333333334 x = 0.565194165 + 0.3333333334 Combine like terms: 0.565194165 + 0.3333333334 = 0.8985274984 x = 0.8985274984 Simplifying x = 0.8985274984Subproblem 2
x + -0.3333333334 = -0.565194165 Simplifying x + -0.3333333334 = -0.565194165 Reorder the terms: -0.3333333334 + x = -0.565194165 Solving -0.3333333334 + x = -0.565194165 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + x = -0.565194165 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + x = -0.565194165 + 0.3333333334 x = -0.565194165 + 0.3333333334 Combine like terms: -0.565194165 + 0.3333333334 = -0.2318608316 x = -0.2318608316 Simplifying x = -0.2318608316Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.8985274984, -0.2318608316}Solution
x = {0.8985274984, -0.2318608316}
| 3(3x-4)=-20 | | 28t-23t=100 | | 67w-40w+(-29w)=38 | | n/4-20==1 | | 51g+20g-61g-6g-3g-1=61 | | (2cosx)(-sinx)=0 | | 54/44 | | 1/9(x-6) | | 0=-1/2a-2/3 | | 3x+6=8x+34 | | -3c-(-86c)+6=89 | | x+3y=55 | | 42=-6(-3n+6)+6(n-3) | | y=6x-26 | | 3.5x+14=42 | | -81w-11w-9w+23w-w+6=85 | | 47/X=6-1/X | | 3a^2=6x | | 20+w=32 | | (2y+8)(2y+8)=0 | | 30p-11p+15p-29p=90 | | -6+2(5-4x)=22-2x | | -6(-2x+2)+4(3+4x)=28 | | 10xt=1.8654 | | (a+6)(a^2-8a+8)=0 | | 6m^2+66m+121=0 | | 3.0=0.4m-2+0.2m | | 8w-3w-4w-1=32 | | (7y)^1/3 | | 10xt= | | 5x+10+x=-8 | | (5x+3)(2x-6)=0 |